Assessing the impact of cluster frontline demonstrations on yield and economic returns of mustard in Yamunanagar, Haryana: MUSTARD YIELD BOOST VIA CLUSTER DEMONSTRATIONS - SANDEEP RAWAL; ARADHANA BALI; ANIL KUMAR; VEER SAIN; AJIT SINGH; KARAN SINGH SAINI; VISHAL GOEL; NARINDER KUMAR GOYAL (Journal of Oilseeds Research, 2026)
The study was carried out during 2021-22, 2022-23, and 2023-24 to assess the impact of Cluster Front Line Demonstrations (CFLDs) on production and productivity enhancement of the mustard crop. CCSHAU-KVK, Yamunanagar conducted a total of 302 demonstrations in selected clusters with GPS locations over an area of 130 ha in the district of Yamunanagar of Haryana. The yield performance data and economics of demonstration and farmers’ practice plots were compiled and analyzed for the calculation of gap analysis, costs, and returns. The critical inputs were identified in existing production technology through personal interaction, group meetings, and discussions with farmers and the KVK Scientists team. The improved technologies consist of improved variety, soil testing, seed treatment, mechanized sowing, integrated nutrient and weed management, and pest and disease management. The average yield of improved technology demonstrations and farmers’ practices was recorded as 17.80 q/ha and 14.40 q/ha, respectively. Overall, the 19.10% increase in yield was found in demonstration plots over check plots. The average of the technology gap, extension gap, technology index, and additional return was found as 2.20 q/ha, 3.40 q/ha, 11%, and ` 11420/ha, respectively. An average net return of ` 42140/ha was found in demonstration plots as compared to ` 30720/ha in farmers’ practices, and an average B:C ratio of 2.65 and 2.28 was recorded in demonstration and farmers’ practice plots, respectively. The higher yields and returns in demonstrations indicated that the production and productivity of mustard in farmers’ fields increased with the adoption of improved technologies. The results revealed that the CFLDs by interventions of scientific technologies gave positive effects on production and productivity in mustard crop cultivation.